2006
DOI: 10.1007/s11746-006-1205-z
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of fractal dimensions of fat crystal networks

Abstract: The rheological properties of fat-structured products are determined by the microstructure of their fat crystal networks, which can be quantified by using microscopical and rheological techniques. Of particular interest to this study is the quantification of the fractal dimension of the network using these two techniques. Fractal dimensions determined by polarized light microscopy include box-counting, particle-counting, and Fouriertransform fractal dimensions, whereas the fractal dimensions determined by smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…As Tang et al reported, one of the factors influencing D box is area fraction of crystalline mass. 32 It is evident from Table 4 that there is more filled area in the CI blends compared with the EI blends. Moreover, our previous paper showed there is a correlation between area fraction and D box .…”
Section: Sfc and Rheological Propertiesmentioning
confidence: 92%
See 2 more Smart Citations
“…As Tang et al reported, one of the factors influencing D box is area fraction of crystalline mass. 32 It is evident from Table 4 that there is more filled area in the CI blends compared with the EI blends. Moreover, our previous paper showed there is a correlation between area fraction and D box .…”
Section: Sfc and Rheological Propertiesmentioning
confidence: 92%
“…D box is less sensitive to area fraction when the size of crystals becomes large and it is not sensitive to crystal size when the area fraction is high. 32 Figure 11 shows that D box increases with increasing SFC (P < 0.0001). However, the sensitivity of this method decreases at high concentrations of hard stock.…”
Section: Sfc and Rheological Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Tang and Marangoni [12] studied how each microstructural factor individually affected D b , D f , and D FT separately in 2D space through computer simulation. In this paper, we built on our previous simulation study and used computer simulation to show how each of the microstructural factors, such as crystal size, area fraction (AF) and distribution orderliness (randomly distribution or even distribution) of fat crystals affect the fractal dimensions of the fat crystal networks in 3D space.…”
Section: Introductionmentioning
confidence: 99%
“…17,24 The fractal dimensions determined by microscopy describe the combined effects of morphology and spatial distribution patterns of the fat crystals within the network and are sensitive to the dimensionality of the embedding space. [25][26][27] In the study on the rheological properties of colloidal gel networks, Shih et al 28 considered a three-dimensional colloidal network as being composed of interconnected flocs, and the fractal dimension was used to quantify the relationship between the average floc size and the particle concentration of the colloidal network. Based on the relative value of the elastic constant of the interfloc links to that of the flocs, two regimes were identified: the strong link regime, where the elastic constant of the interfloc links is larger than that of the flocs, and weak link regime, where the elastic constant of the interfloc links is smaller than that of the flocs.…”
Section: Fractal Modelmentioning
confidence: 99%